Prevention of Atrial Fibrillation in High-risk Patients Undergoing Lung Cancer Surgery: The PRESAGE Trial. Issue 2 (August 2016) - Cardinale, Daniela; Sandri, Maria T.; Colombo, Alessandro; Salvatici, Michela; Tedeschi, Ines; Bacchiani, Giulia; Beggiato, Marta; Meroni, Carlo A.; Civelli, Maurizio; Lamantia, Giuseppina; Colombo, Nicola; Veglia, Fabrizio; et al.
Abstract : Objective: We performed a prospective, randomized clinical study to assess whether prophylactic treatment with metoprolol or losartan, initiated soon after lung cancer surgery in patients with elevated N-terminal pro-brain natriuretic peptide (NT-proBNP) levels, reduces the incidence of postoperative atrial fibrillation. Background: Postoperative atrial fibrillation is a well recognized complication after lung cancer surgery, with an incidence as high as 30%. Perioperative increase of NT-proBNP has been demonstrated to be a strong independent predictor of postoperative atrial fibrillation in this setting. Methods: NT-proBNP concentration was measured 24 hours before surgery and soon after surgery in 1116 patients. Three hundred twenty (29%) patients showed a high NT-proBNP value and were enrolled: 108 were assigned to the metoprolol group, 102 to the losartan group, and 110 to the control group. Results: Overall, the incidence of postoperative atrial fibrillation was 20% (n = 64); it was significantly lower in the metoprolol and losartan groups compared with the control group [6%, 12%, and 40%, respectively; relative risk 0.19, 95% confidence intervals (CIs), 0.09–0.37; P < 0.001 in the metoprolol group; and 0.29, 95% CI, 0.16–0.52; P < 0.001 in the losartan group). No significant difference was found when the metoprolol and losartan groups were directly compared ( P = 0.21). Conclusions: A prophylactic treatment with metoprolol or losartan, initiated soon after lung cancer surgery in patients with high NT-proBNP levels, significantly reduced the occurrence of postoperative atrial fibrillation.